2012
DOI: 10.1007/s11434-012-5328-3
|View full text |Cite
|
Sign up to set email alerts
|

Associations between gene polymorphisms in two crucial metabolic pathways and growth traits in pigs

Abstract: Propanoate metabolism and fatty acid metabolism are crucial metabolic pathways in vivo that have been studied extensively and have shown a significant influence on the growth and diseases of animals. In order to identify the essential genes significantly associated with porcine growth traits at the pathway level, we selected 14 candidate genes with 58 SNPs, including 24 tag SNPs and 34 predicted SNPs, in the two essential pathways to test using the SNaPshot mini-sequencing method. Association analysis was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…) and Acaa2 (Yang et al. ) genes in delipated embryos also explained a lower production of ATP after delipation. On the other hand, the increased expression of Glut1 gene was also observed in porcine embryos after FAO inhibition, suggesting that alternate energy pathways were upregulated when FAO was blocked (Paczkowski et al.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…) and Acaa2 (Yang et al. ) genes in delipated embryos also explained a lower production of ATP after delipation. On the other hand, the increased expression of Glut1 gene was also observed in porcine embryos after FAO inhibition, suggesting that alternate energy pathways were upregulated when FAO was blocked (Paczkowski et al.…”
Section: Discussionmentioning
confidence: 94%
“…However, large lipid droplets were removed and only the small lipid droplets are left in the delipated oocytes after delipation (Niu et al 2015). What is more, the decreased expression of Acadsb (Jiang et al 2014) and Acaa2 (Yang et al 2012) genes in delipated embryos also explained a lower production of ATP after delipation. On the other hand, the increased expression of Glut1 gene was also observed in porcine embryos after FAO inhibition, suggesting that alternate energy pathways were upregulated when FAO was blocked (Paczkowski et al 2013) such as glucose metabolism, where Glut1 was involved (Kahn et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The propanoate metabolic process is involved in crucial in vivo metabolic pathways and is associated with the TCA cycle. 56 In addition, beta-alanine is a precursor of the oxidative substrate acetylcoenzyme A. 57 Pathway screening analysis showed that pantothenate and acetyl-CoA biosynthesis was another key metabolic pathway implicated in the response to kiwi wine consumption, with the prominent serological metabolites being beta-alanine and L-cysteine.…”
Section: Discussionmentioning
confidence: 99%
“…The main direction of pig breeding is to provide new genetic knowledge about pig traits and focus on the identification and prediction of individual genes responsible for the reproduction, growth and meat traits (Fan et al, 2012;Yan et al, 2013;Leonova et al, 2015;Mihailov et al, 2014). Growth Hormone (GH), also known as somatotropin, is synthesized in the anterior pituitary (adenohypophysis in somatotropic cells).…”
Section: Introductionmentioning
confidence: 99%